Gastro-Intestinal Tract Complications During Antithrombotic Therapy - E. V. Moroz; E. N. Artemkin; E. V. Kryukov; V. A. Chernetsov (Общая реаниматология)
Use of antithrombotic aids (ATA)  significantly  impact  the prevention of life-threatening cardiovascular complications. ATA applications, however, are associated with a wide range of adverse digestive system responses. Due to, continuously growing clinical use of ATA this problem has become a current challenge of contemporary medicine.Purpose of the study was to evaluate the patterns of digestive system damage in patients receiving ATA.Materials and Methods. 672 patients were examined, 91.0% males, 46.7±17.4 years of age, who had digestive system changes that  occurred  due to ATA intake. 71 patients were admitted for treatment after gastrointestinal (GI) bleeding; other  patients were hospitalized  because of disorders  of the digestive  system or erosive and ulcerous changes of the digestive  system detected by endoscopy.  The following parameters were  evaluated:  GI bleeding sources, character of complaints,  the endoscopic patterns due to intake of different ATAs (low doses of aspirin, warfarin, clopidogrel,  dabigatran, rivaroxaban, low-molecular  heparin,  combined  therapy), and of risk factors for GI complications.Results. The sources of GI bleeding (n=71) included  gastric ulcers and/or erosions (39.4%), duodenum ulcers and/or erosions (21.1%), colon ulcers and/or erosions (28.2%), unknown  (11.3%). The majority of 672 patients noticed  various  complaints:  sensation  of heaviness  in epigastrium (62.8%),  gastralgia  (46.7%),  burning  sensation (34.3%). Endoscopy found erosive esophagitis (13.2%), ulcers in stomach and/or duodenum (11.6%), multiple (  10) erosions of stomach or duodenum (17.1%), sporadic erosions of stomach or duodenum (24.4%). In 32.3% cases no erosive or ulcerous alterations were found. H. pylori was identified in 57.9% of patients. There was no significant difference in character of alterations in the upper digestive system between patients who received different ATA treatment, except of frequent erosive esophagitis in those patients who received dabigatran (16.8%). The elderly age (  65 years), ulcer history, concomitant intake of NSAIDS, H. pylori presence, and smoking habit were associated with a higher occurrence of pathological alterations of digestive system. Presence  of gastralgia  did not correlate with the development of erosive and ulcerous alterations.Conclusion. In majority of patients who received ATA, the commonly observed erosive and ulcerous alterations in the digestive system might become a source of bleeding.